Towards a semantics for argumentative systems - Stankevicius, Alejandro G. (2006)
Defeasible argumentation is one of the approaches that attempt to address the challenges arising when we reason defeasibly, with several formalisms in the literature reaching a mature state. Nowadays, several of them started shifting their semantics towards a dialectical characterization. Therefore, we believe that a sufficiently generic model of the process of dialectical reasoning could also serve as an abstract model of what happens inside an argumentative systems. To that end, in this article we lay the foundations required for such a generic model, proposing a line of research whose central objective is attaining that abstract semantics for argumentative systems.